BET1 variants establish impaired vesicular transport as a cause for muscular dystrophy with epilepsy. Issue 12 (15th November 2021) - Donkervoort, Sandra; Krause, Niklas; Dergai, Mykola; Yun, Pomi; Koliwer, Judith; Gorokhova, Svetlana; Geist Hauserman, Janelle; Cummings, Beryl B; Hu, Ying; Smith, Rosemarie; Uapinyoying, Prech; Ganesh, Vijay S; et al.
Abstract: BET1 is required, together with its SNARE complex partners GOSR2, SEC22b, and Syntaxin‐5 for fusion of endoplasmic reticulum‐derived vesicles with the ER‐Golgi intermediate compartment (ERGIC) and the cis ‐Golgi. Here, we report three individuals, from two families, with severe congenital muscular dystrophy (CMD) and biallelic variants in BET1 (P1 p.(Asp68His)/p.(Ala45Valfs*2); P2 and P3 homozygous p.(Ile51Ser)). Due to aberrant splicing and frameshifting, the variants in P1 result in low BET1 protein levels and impaired ER‐to‐Golgi transport. Since in silico modeling suggested that p.(Ile51Ser) interferes with binding to interaction partners other than SNARE complex subunits, we set off and identified novel BET1 interaction partners with low affinity for p.(Ile51Ser) BET1 protein compared to wild‐type, among them ERGIC‐53. The BET1/ERGIC‐53 interaction was validated by endogenous co‐immunoprecipitation with both proteins colocalizing to the ERGIC compartment. Mislocalization of ERGIC‐53 was observed in P1 and P2's derived fibroblasts; while in the p.(Ile51Ser) P2 fibroblasts specifically, mutant BET1 was also mislocalized along with ERGIC‐53. Thus, we establish BET1 as a novel CMD/epilepsy gene and confirm the emerging role of ER/Golgi SNAREs in CMD. SYNOPSIS: This study describes three individuals with a progressive early‐onset congenital muscular dystrophy, and additional epilepsy in one, caused by biallelic variants in the BET1 gene. BET1, along with its SNARE complex partners, is essential for ER‐to‐Golgi trafficking. In Family 1, compound heterozygous variants p.(Asp68His)/p.(Ala45Valfs*2) cause aberrant splicing and frameshifting, resulting in very low BET1 protein levels. Variants in Family 2 (homozygous p.(Ile51Ser)) do not impact BET1 protein levels, interactions with ER‐to‐Golgi SNARE complex members, or SNARE function in yeast. Mutant Ile51Ser BET1 shows massively reduced binding of the novel Bet1 interaction partner ERGIC‐53, which is also mislocalized in patient fibroblasts. There is a significant slowing of Golgi‐reconstitution in patient fibroblasts and impaired ER‐to‐Golgi trafficking in HeLa cells. This study adds to the emerging role of ER/Golgi SNARE dysfunction in the causation of muscular dystrophy. Abstract : This study describes three individuals with a progressive early‐onset congenital muscular dystrophy, and additional epilepsy in one, caused by biallelic variants in the BET1 gene. BET1, along with its SNARE complex partners, is essential for ER‐to‐Golgi trafficking.